2007
DOI: 10.1158/0008-5472.can-06-4257
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Potentiates Antitumor Activity of Gemcitabine in an Orthotopic Model of Pancreatic Cancer through Suppression of Proliferation, Angiogenesis, and Inhibition of Nuclear Factor-κB–Regulated Gene Products

Abstract: Gemcitabine is currently the best treatment available for pancreatic cancer, but the disease develops resistance to the drug over time. Agents that can either enhance the effects of gemcitabine or overcome chemoresistance to the drug are needed for the treatment of pancreatic cancer. Curcumin, a component of turmeric (Curcuma longa), is one such agent that has been shown to suppress the transcription factor nuclear factor-KB (NF-KB), which is implicated in proliferation, survival, angiogenesis, and chemoresist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
415
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 551 publications
(449 citation statements)
references
References 45 publications
31
415
0
3
Order By: Relevance
“…We have found that (a) the combination of curcumin and gemcitabine inhibits pancreatic cancer growth in nude mice by inhibiting NF-kB regulated gene expression, cell proliferation, and angiogenesis [144]; (b) the combination of curcumin and docetaxel is effective against human ovarian cancer in nude mice [142]; (c) curcumin can suppress the growth of human glioblastoma in rodents [77]; and (d) curcumin sensitizes colon cancers in nude mice to oxaliplatin [137]. In addition, other recent studies have shown that curcumin sensitizes prostate cancers to chemotherapeutics and radiation by downregulating expression of the MDM2 oncogene [82].…”
Section: Curcumin Exhibits Antitumor Activity In Animalsmentioning
confidence: 99%
“…We have found that (a) the combination of curcumin and gemcitabine inhibits pancreatic cancer growth in nude mice by inhibiting NF-kB regulated gene expression, cell proliferation, and angiogenesis [144]; (b) the combination of curcumin and docetaxel is effective against human ovarian cancer in nude mice [142]; (c) curcumin can suppress the growth of human glioblastoma in rodents [77]; and (d) curcumin sensitizes colon cancers in nude mice to oxaliplatin [137]. In addition, other recent studies have shown that curcumin sensitizes prostate cancers to chemotherapeutics and radiation by downregulating expression of the MDM2 oncogene [82].…”
Section: Curcumin Exhibits Antitumor Activity In Animalsmentioning
confidence: 99%
“…We then assessed the expression of cyclin D1, which plays important role in tumor cell proliferation and cell cycle progression from G 1 phase to S phase; and Bcl-2, which is involved in tumor survival and chemoresistance in pancreatic cancer cells [17] , because both of the genes can be regulated by GSK-3β in pancreatic cancer cells [6] . RT-PCR analysis ( Figure 6A) indicates that mRNA level of cylcin D1 and Bcl-2 are significantly suppressed by ASA in a dose-dependent manner in 24 h. Western blotting ( Figure 6B) shows that ASA also reduces the protein level of cyclin D1 and Bcl-2.…”
Section: Asa Downregulates the Expression Of Cyclin D1 And Bcl-2mentioning
confidence: 99%
“…Acquired resistance toward gemcitabine might partially be mediated by upregulation of the apoptosis inhibitors Bcl-2, Bcl-xL, Mcl-1, survivin and the cellular inhibitor of apoptosis protein-1 (cIAP-1). 10,11,[26][27][28] The proapoptotic proteins BNIP3 and Bax related to apoptosis induction in gemcitabine-resistant cell lines with a significant tumor regression. Erkan et al and Akada et al showed that silencing of BNIP3 by small interfering RNA (siRNA) correlated with increased chemoresistance.…”
Section: Apoptosismentioning
confidence: 99%
“…12 The treatment by Wack et al with adenoviral systems for proapoptotic Bax and TNF-related apoptosis-inducing ligand (TRAIL) expression targeting, using the human telomerase reverse transcriptase (hTERT) promoter, resulted in high-level expression of Bax and TRAIL, genes directly related to apoptosis induction in gemcitabine-resistant cell lines with a significant tumor regression and prolongation of in vivo survival. 31 27,28,33 Expression levels of antiapoptotic proteins such as Bcl-2 and Bcl-xL were reported to be upregulated by the transcription factor NFjB, which additionally transactivates a number of other antiapoptotic genes, such as cIAPs. Data of Muerkoster et al imply that the antiinflammatory drug sulfasalazine sensitizes PC cells to chemotherapy in vivo by inhibition of NFjB and stimulation of apoptosis.…”
Section: Apoptosismentioning
confidence: 99%